FINANCIAL PERFORMANCE ANALYSIS BEFORE AND AFTER THE IMPLEMENTATION OF FINANCIAL MANAGEMENT PATTERNS OF REGIONAL GENERAL SERVICES AGENCY AT CUT MEUTIA REGIONAL GENERAL HOSPITAL, ACEH UTARA REGENCY - Rolinda, Cut; Naz’aina, Naz’aina; Khaddafi, Muammar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
This study analyzed differences in financial performance before and after the implementation of the Financial Management Pattern of the Regional Public Service Agency (PPK-BLUD) at Cut Meutia Public Hospital, North Aceh Regency. Financial performance was proxied by the ratio of profitability, liquidity, solvency, and activity. The periods used were 2012-2015 (Before KDP-BLUD) and 2016-2019 (After KDP-BLUD). This study used secondary data in the form of quantitative data. The data analysis method used was Paired T-Test. The results showed that in financial performance ratios, there were significant differences in the ratio of profitability, liquidity, and activity before and after the implementation of PPK-BLUD, but the solvency ratio did not differ before and after the implementation of PPK-BLUD at Cut Meutia Hospital, North Aceh Regency.